Dielectric Relaxation and Beyond Limiting Behavior of Alternating‐Current Conductivity in a Supermolecular Ferroelectric. Issue 4 (29th January 2019) - Tong, Yuan‐Bo; Tian, Zheng‐Fang; Duan, Hai‐Bao; Zhu, Zhong‐Peng; Hong, Tian‐Yu; Zhao, Shun‐Ping; Yang, Jing‐Kui
Abstract: A cyclen‐based hybrid supermolecule crystal, [(FeCl2 )(cyclen)]Cl (1 ), where cyclen=1, 4, 7, 10‐tetraazacyclododecane, was prepared using a liquid–liquid diffusion approach. The variable crystal structures exhibit that compound 1 belongs to an orthorhombic crystal system, Pna 21 space group (point group C 2 V ) in the temperature range of 150–400 K. This hybrid supermolecule shows a dielectric relaxation behavior around room temperature, and the ferroelectric nature of1 has been directly verified by hysteresis measurements. In addition, the AC (alternating current) conductivity study reveals that the1 displays a beyond limiting behavior. These interesting findings are for the first time reported in the field of supermolecular ferroelectrics. This study may open a new way to construct supermolecular ferroelectrics and give insights into their conductor behavior. Abstract : Have a little relaxation : A supermolecular crystal obtained by a simple diffusion route shows dielectric relaxation and ferroelectric behavior around room temperature. The AC conductivity study reveals that the hybrid crystal displays a beyond limiting behavior. These characteristics coexisting in a supermolecule have rarely been reported.